Activity of drug-loaded tumor-penetrating microparticles in peritoneal pancreatic tumors - Lu, Ze; Tsai, Max; Wang, Jie; Cole, David J; Wientjes, M Guillaume; Au, Jessie L-S (Current cancer drug targets, 2014)
Intraperitoneal (IP) chemotherapy confers significant survival benefits in cancer patients. However, several problems, including local toxicity and ineffectiveness against bulky tumors, have prohibited it from becoming a standard of care. We have developed drug-loaded, polymeric tumor-penetrating microparticles (TPM) to address these problems. Initial studies showed that TPM provides tumor-selective delivery and is effective against ovarian SKOV3 tumors of relatively small size (<50 mg). The present study evaluated whether the TPM activity extends to other tumor types that are more bulky and have different morphologies and disease presentation. We evaluated TPM in mice bearing two IP human pancreatic tumors with different growth characteristics and morphologies (rapidly growing, large and porous Hs766T vs. slowly growing, smaller and densely packed MiaPaCa2), and at different disease stage (early stage with smaller tumors vs. late stage with larger tumors plus peritoneal carcinomatosis). Comparison of treatments with TPM or paclitaxel in Cremophor micelles, at equi-toxic doses, shows, in all tumor types: (a) higher paclitaxel levels in tumors (up to 55-fold) for TPM, (b) greater efficacy for TPM, including significantly longer survival and higher cure rate, and (c) a single dose of TPM was equally efficacious as multiple doses of paclitaxel/Cremophor. The results indicate tumor targeting property and superior antitumor activity of paclitaxel-loaded TPM are generalizable to small and large peritoneal tumors, with or without accompanying carcinomatosis.